Income Elasticity of Imports and External Constraint in Periods of Commodity Export Boom: Evidence for the Brazilian Economy (Desarrollo Económico. Revista de Ciencias Sociales, 2023)
The work proposal includes verifying: i) whether the increase in the income elasticity of demand for imports (IEDI) in Brazil (between 1997q1 and 2018q4 ) can be explained by the increase in exports; ii) whether this could have occurred as a result of the increase in commodity exports; iii) the mechanisms by which the increase in IEDI occurred, whether through final consumption goods or through intermediate goods; iv) whether this should be considered in models that explain economic growth through the performance of the balance of payments (Thirlwall's Law). Then, to test this, we propose estimates a modified version of the multi-sectoral Thirlwall Law (MSTL). The vector autoregressive (VAR) methodology and the vector error correction model (VECM) were used in the estimations. The results showed that the growth of commodity exports has a significant impact on the increase in the IEDI in the analyzed period, which limits the possibilities for the Brazilian economy to reach a balanced growth trajectory with a higher growth rate in the long term.
Keywords: Balance-of-payments-constrained growth. income elasticities of sectoral trade. technological intensity. broad economic categories